Determinasi Keberhasilan Digital government pada Pemerintah Daerah: Tinjauan Sistematis atas Faktor Organisasi dan Tata Kelola - Putri Rizkiyah; Rina Tjandra Kirana DP (GLOBAL SCIENTS PUBLISHER, 2026)
Digital transformation in local governments has become a central focus of public sector reform. However, existing studies often examine the determinants of Digital government success separately, such as organizational capacity, institutional pressure, or governance mechanisms. This study synthesizes the main factors influencing Digital government success at the local level and proposes an integrated framework explaining their interconnections. A qualitative Systematic Literature Review (SLR) was conducted following PRISMA 2020 guidelines. From 482 identified records, 36 peer-reviewed articles published between 2021 and 2026 met the inclusion criteria and were analyzed. The findings indicate that Digital government success is multidimensional, driven by three interconnected dimensions: organizational capacity, institutional pressures, and collaborative governance. Organizational factors such as leadership and digital capabilities form the foundation, while institutional pressures act as catalysts and collaborative governance supports sustainability. The study proposes an integrated conceptual model highlighting Digital government success as the result of dynamic interactions among these factors.